A real-time shop floor control system: an integrated RFID approach. (4th June 2007) - Poon, T.C.; Choy, K.L.; Lau, H.C.W.
In the past, it was difficult to have a clear picture of the present status of production in shop floor. Many enterprises have adopted bar-code-based Shop Floor Control Systems (SFCSs) for monitoring the production status. However, the deficiency of such systems is that immediate situation cannot be reflected easily. As a result, planned production schedules cannot be fulfilled due to frequent job interruptions caused by machine breakdowns or a shortage of materials. In this paper, a Radio Frequency Identification- (RFID-)based Decision Support System (RDSS) is proposed for the shop floor management to keep track of resources, monitor the throughput rate and make instant decisions for problem solving. The proposed system integrates the technologies of RFID and Rule-Based Reasoning (RBR) with production mathematical algorithm to help monitor shop floor operations. Through pilot running of RDSS in the ABC Limited, a significant improvement in terms of shop floor responsiveness was achieved.